Política de educação profissional nos governos do Rio Grande do Sul: que tijolos a (des)constroem? - Duarte, Mareliza Fagundes de Araujo (2022)
The research aims to analyze the proposals and actions of the governments of the Stateof RioGrande do Sul, for Professional Education, in the period between the years 1971 to2021. It isincluded in the Research Line LP1: Policies and Management in Professional andTechnological Education of the Graduate Program in Professional and TechnologicalEducation, PPGEPT, prepared together with the research group TransformaAção- GroupofStudies and Research in Public Policies and Pedagogical Work in Professional EducationandKairós - Group of Studies and Research on Work , Education and Public Policy. Thetitleresorts to the use of the word “bricks” as a metaphor to highlight the need to understandtheconstruction/deconstruction of government proposals and actions with regard to ProfessionalEducation. The questioning of the proposal is how are the proposals and actions of thegovernments of the State of Rio Grande do Sul for Professional Education configured, intheperiod between the years 1971 to 2021? The specific objectives were thus defined: tohistoricize the EPT policy in Brazil and RS; contextualize the proposals and actions oftheState government regarding Professional Education in RS, from 1971 to 2021 and, finally,understand how the educational policy and the provision of Professional Educationwereconstituted in the research period. The research was a fifty-year study of the GovernmentsofRS, through documentary research and the analysis of government plans and messagestotheLegislative Assembly by the Heads of State, which was carried out through content analysis(BARDIN, 2019). Data were organized into four phases and presented in chapters, includingnational and state historicity, highlights of the plans and messages fromthe governmentsthatmake up each phase: the years 1971, the redemocratization of Brazil and the CitizenshipConstitution in 1988; Professional Education in the State Constitution and fromSimontothepopular government; Professional Education from the expansion of the Federal Network: theRS against the grain of interests; and Professional Education and the worsening of thecrisisinRS. It is concluded that PE was offered in the RS State Network in all 13(thirteen)Governments surveyed, from Triches to Leite, either in the form of projects and/or programs,with resources from federal funds or from the State Treasury. The Liberato SalzanoVieiradaCunha Technical School Foundation has been a reference in the last 50 years of governmentas a gift from EP. The research points out that in the popular governments of Collares, Olívioand Tarso, PE was a priority in the management of these governments, includinginthecontext, a specific project on the proposed State policy for Professional Education. However,in the documents, specific policies (the government's) for PE were not found. Therefore, itwas proved that the PE in the State Network is now advancing or is just being offeredthereand following the policy of the federal governments.